rs62139665 Polymorphism in the Promoter Region of EpCAM Is Associated With Hepatitis C Virus-Related Hepatocellular Carcinoma Risk in Egyptians - Motawi, Tarek Mohamed Kamal; Sadik, Nermin Abdel Hamid; Sabry, Dina; Fahim, Sally Atef; Shahin, Nancy Nabil (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is a universal health problem that is particularly alarming in Egypt. The major risk factor for HCC is hepatitis C virus (HCV) infection which is a main burden in Egypt. The epithelial cell adhesion molecule (EpCAM) is a stem cell marker involved in the tumorigenesis and progression of many malignancies, including HCC. We investigated the association of -935 C/G single nucleotide polymorphism in EpCAM promoter region (rs62139665) with HCC risk, EpCAM expression and overall survival in Egyptians. A total of 266 patients (128 HCV and 138 HCC cases) and 117 age- and sex-matched controls participated in this study. Genotyping, performed using allelic discrimination and confirmed by sequencing, revealed a significant association between EpCAM rs62139665 and HCC susceptibility, with higher GG genotype and G allele distribution in HCC patients than in non-HCC subjects. Such association was not detected in HCV patients compared to controls. EpCAM gene expression levels, determined in blood by RT-qPCR, and its serum protein expression levels, determined by ELISA, were significantly higher in GG relative to GC+CC genotype carriers in HCV and HCC patients in a recessive model. ROC analysis of EpCAM protein levels revealed significant discriminatory power between HCC patients and non-HCC subjects, with improved diagnostic accuracy when combining α-fetoprotein and EpCAM compared to that of α-fetoprotein alone. Altogether, EpCAM rs62139665 polymorphism is significantly associated with HCC and with EpCAM gene and protein expression levels in the Egyptian population. Moreover, serum EpCAM levels may hold promise for HCC diagnosis and for improving the diagnostic accuracy of α-fetoprotein.